Analisis Kecanduan Menonton YouTube pada Anak Balita Menggunakan Model SEIEdR - Sukmana, Eko Akbar; Firmansyah, Firmansyah; Panjaitan, Dedy Juliandri (Universitas Methodist Indonesia, 2024)
In contemporary society, YouTube addiction in children under five has become an increasingly troubling problem. The purpose of this study is to solve the addiction problem and provide solutions that can be applied in the workplace. A modified SEIEdR (Suspectible-Exposed-Infected-Education-Recovered) model for YouTube watching addiction behavior is used. Identifying assumptions and parameters, creating mathematical models, finding equilibrium points, calculating the basic reproduction number (R0), conducting model stability analysis, and performing simulations using Maple software are all methodological processes. The main findings show that if R0 < 1, the addictive behavior of watching YouTube will decrease over time and will become endemic. In addition, the individual rate values of active and novice viewers who are educated have a significant effect on reducing the population of novice and active YouTube viewers. These simulation results improve our understanding of the dynamics of YouTube viewing addiction and offer practical solutions to this problem.